A convenient method for the synthesis of Imidazo[1,2-a]pyridines with a new approach - Balalaie, Saeed; Rominger, Frank (Synlett, 2018)
A new approach for the efficient synthesis of imidazo[1,2-a]pyridines is described. The synthesis was carried out via the reaction of functionalized 2-aminopyridine that were formed through a three-component reaction and phenacyl bromide derivatives.